2014
DOI: 10.1186/1743-0003-11-130
|View full text |Cite
|
Sign up to set email alerts
|

Postural stabilization during bilateral and unilateral vibration of ankle muscles in the sagittal and frontal planes

Abstract: BackgroundThe purpose was to investigate the postural consequences of proprioceptive perturbation of the Triceps Surae and Peroneus Longus muscles. These muscles are known to control posture respectively in the sagittal and frontal planes during standing.MethodsStandard parameters and the time course of center of pressure (CoP) displacements were recorded in 21 young adults, instructed to maintain their balance during tendon vibration. Following 4 s of baseline recording, three types of vibration (80 Hz) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
2
28
1
2
Order By: Relevance
“…Combined with the tibialis muscles, the peroneus muscles support and stabilize the ankle joint (De Ridder et al 2014. The peroneus longus (PL) is well known to provide lateral stability, and the tibialis anterior (TA) muscle is increasingly activated when the lateral displacement of the tibia is being controlled (Page et al 2010;De Ridder et al 2014;Duclos et al 2014;Pozzi et al 2015). Calf muscles also support anterior/posterior stability of the ankle joint, especially when postural stability is challenged (Vieira et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with the tibialis muscles, the peroneus muscles support and stabilize the ankle joint (De Ridder et al 2014. The peroneus longus (PL) is well known to provide lateral stability, and the tibialis anterior (TA) muscle is increasingly activated when the lateral displacement of the tibia is being controlled (Page et al 2010;De Ridder et al 2014;Duclos et al 2014;Pozzi et al 2015). Calf muscles also support anterior/posterior stability of the ankle joint, especially when postural stability is challenged (Vieira et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The ankle plays a major role in posture and locomotion (Baumhauer et al 1995;Vieira et al 2013;Cattagni et al 2014;Duclos et al 2014;Pozzi et al 2015). Small changes in the center of gravity are corrected by the position of the knee, hip and ankle to maintain the center of gravity in the basal plane (Page et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since we observed a shorter APA phase and a faster A-P CoP velocity when vibration was applied only immediately before gait initiation onset, we suggest that this condition may benefit participants. A CoP position excessive recovery after vibration was already demonstrated by other studies [10,14]: e.g. when vibration on the gastrocnemius was interrupted, an excessive forward CoP recovery in relation to its initial position was observed [10].…”
Section: Discussionmentioning
confidence: 60%
“…However, our results (Figure 1), show that independently of the moment vibration was applied, it induced an improvement in gait initiation performance. This finding indicates that the benefits of vibration on the gait initiation performance are not exclusively explained by post-vibratory effects [10,13,14,28]. Tard et al [29] demonstrated that stimulus-driven attention modifies the gait initiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation